2015
DOI: 10.1111/mono.12147
|View full text |Cite
|
Sign up to set email alerts
|

Vii. Infant Sleep Development From 3 to 6 Months Postpartum: Links With Maternal Sleep and Paternal Involvement

Abstract: The aims of this longitudinal study were to examine (a) development of infant sleep and maternal sleep from 3 to 6 months postpartum; (b) concomitant and prospective links between maternal sleep and infant sleep; and (c) triadic links between paternal involvement in infant caregiving and maternal and infant sleep. The study included 57 families that were recruited during pregnancy. Maternal and infant sleep was assessed using actigraphy and sleep diaries for 5 nights. Both fathers and mothers completed a quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 42 publications
6
84
7
Order By: Relevance
“…It is possible that nocturnal wakefulness as measured here again may be an inaccurate representation of a sleep problem in an infant, or that self-reporting of the wakefulness is biased. However if it is accurate, then the data presented here is inconsistent with past findings (Tikotzky et al, 2015;Meijer & van den Wittenboer, 2007).…”
Section: Discussioncontrasting
confidence: 57%
“…It is possible that nocturnal wakefulness as measured here again may be an inaccurate representation of a sleep problem in an infant, or that self-reporting of the wakefulness is biased. However if it is accurate, then the data presented here is inconsistent with past findings (Tikotzky et al, 2015;Meijer & van den Wittenboer, 2007).…”
Section: Discussioncontrasting
confidence: 57%
“…In humans, father presence during early development is associated with decreased risk for various psychopathologies and increased well-being of the children (Sarkadi et al, 2008; McLanahan et al, 2013; Tikotzky et al, 2015), whereas father absence can lead to negative outcomes including the development of depressive symptoms and externalizing behaviors (Phares and Compas, 1992; Culpin et al, 2013; McLanahan et al, 2013). In the present study, using the socially monogamous prairie voles which naturally display both maternal and paternal behaviors, we found that paternal deprivation (PD) during early development has long-lasting effects on social affiliation of the offspring when they became adults, and this effect is behavior-specific.…”
Section: Discussionmentioning
confidence: 99%
“…While evidence suggests that both infant and maternal sleep disruptions are independently associated with postpartum depression (e.g., Dennis & Ross, 2005), little is known about the effect of the interplay between maternal and infant sleep on maternal depression and the mother-child relationship across the first years of life. Moreover, although many have examined concurrent and predictive links between postpartum maternal and infant sleep (e.g., Tikotzky, Sadeh, Volkovich, Manber, Meiri, & Shahar, 2015), to our knowledge, little is known about the ways in which mothers’ typical sleep patterns affect infant sleep processes and the emergence of postpartum depression. The current study examined the interactive effects of infants’ sleep and mothers’ typical prenatal sleep patterns and the ways in which the match between infant and mother sleep influences maternal depressive symptoms and later mother-child attachment security.…”
Section: Introductionmentioning
confidence: 99%